2020
DOI: 10.1186/s12935-020-01496-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA circ_0000517 regulates hepatocellular carcinoma development via miR-326/IGF1R axis

Abstract: Background: Circular RNAs (circRNAs) play vital roles in hepatocellular carcinoma development. However, the role and mechanism of circRNA hsa_circ_0000517 (circ_0000517) in hepatocellular carcinoma development were largely unknown. Methods: 45 paired tumor and adjacent nontumor samples were collected from hepatocellular carcinoma patients. The levels of circ_0000517, miR-326 and insulin-like growth factor type 1 receptor (IGF1R) were detected via quantitative reverse transcription polymerase chain reaction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Evidence has suggested that microRNA (miRNA/miR) expression is abnormal in different types of tumor tissues and it is well-known that miRNAs play notable roles in tumor development and cancer therapy (19). To date, low expression levels of miR-326 have been observed in HCC tissues and cell lines, and miR-326 has been found to exert a regulatory effect on the proliferation, migration and invasion of HCC cells (20). Nevertheless, to the best of the authors' knowledge, there is currently no evidence regarding the interaction between PCAT6 and miR-326 in liver cancer.…”
Section: Lncrna Pcat6 Facilitates Cell Proliferation and Invasion Via Regulating The Mir-326/hnrnpa2b1 Axis In Liver Cancermentioning
confidence: 99%
“…Evidence has suggested that microRNA (miRNA/miR) expression is abnormal in different types of tumor tissues and it is well-known that miRNAs play notable roles in tumor development and cancer therapy (19). To date, low expression levels of miR-326 have been observed in HCC tissues and cell lines, and miR-326 has been found to exert a regulatory effect on the proliferation, migration and invasion of HCC cells (20). Nevertheless, to the best of the authors' knowledge, there is currently no evidence regarding the interaction between PCAT6 and miR-326 in liver cancer.…”
Section: Lncrna Pcat6 Facilitates Cell Proliferation and Invasion Via Regulating The Mir-326/hnrnpa2b1 Axis In Liver Cancermentioning
confidence: 99%
“…12 Besides, circ_0000517 knockdown decreases HCC cell viability, colony formation, cell migration, cell invasion, and glycolysis by mediating the miR-326/ insulin-like growth factor 1 receptor (IGF1R) axis. 13 Although existing evidence is quite insufficient, these experimental studies of circ_0004913 and circ_0000517 may explain their potential clinical values found in our study to some extent.…”
Section: Discussionmentioning
confidence: 56%
“…[9][10][11] Previously, three circRNAs (circ_0004913, circ_0008160, and circ_0000517) are reported to be dysregulated in HCC tissues (GSE94508 and GSE97332), and these three circRNAs are also confirmed by qPCR to be dysregulated in both HCC tissues and HCC cells; more interestingly, two of them are revealed to be potential regulators of HCC pathogenesis as well. [12][13][14] Nevertheless, the possible clinical values of these three circRNAs remain to be elusive in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, circ-PRMT5 promotes HCC proliferation, migration and glycolysis by miR-188-5p sponging to regulate HK2 (104). Furthermore, circ-0000517 promotes HCC progression and glycolysis via miR-326/IGF1R (105). In total, circRNAs are novel ncRNAs, and only a few studies have reported on the altered metabolic reprogramming regulated by circRNAs in HCC.…”
Section: Regulation Of Metabolism In Hcc By Circrnasmentioning
confidence: 99%